Integration of Islamic Finance and Green Economy in Realizing Sustainable Finance in Indonesia - Misbachul Munir (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2025)
Background. Integrasi keuangan syariah dan ekonomi hijau menjadi isu strategis dalam upaya mewujudkan keuangan berkelanjutan di Indonesia, seiring dengan meningkatnya kebutuhan pembiayaan untuk transisi menuju pembangunan rendah karbon. Aim. This study aims to analyze the role, challenges, and opportunities of Islamic financial integration in supporting the implementation of a green economy in Indonesia, particularly in the context of national policies and the development of the Islamic financial industry. Method. This study employed a descriptive qualitative approach with library research. Data were obtained from secondary sources, including scientific books, accredited journal articles, policy documents, and official reports from national and international institutions such as the Financial Services Authority, Bank Indonesia, the Ministry of Finance, and the Global Green Growth Institute. Data analysis was conducted using content analysis techniques to identify the alignment between Islamic finance principles, green economy objectives, and the applicable regulatory framework. Result. The research findings demonstrate that Islamic finance aligns normatively with green economic principles, particularly in terms of fairness, sustainability, and orientation toward the real sector. Instruments such as green sukuk, profit-sharing financing, and Islamic fintech have significant potential to support inclusive green financing. However, this integration still faces various challenges, including limited green financial literacy, the lack of standardized Sharia-based ESG indicators, and the national economy's dependence on fossil fuels. This research recommends strengthening regulations, innovating green Islamic financial products, and utilizing digital technology as key strategies to accelerate Islamic finance's contribution to green economic development in Indonesia.